Implementation Draft Programming Oriented Objects in Parking System Application using Language Programming Java - Siambaton, Muhammad Zulfansyuri; Azis, Zainal; Harahap, Tua Halomoan (Tsabit Journal of Computer Science, 2024)
The development of Information Technology has become increasingly rapid. Many agencies or companies that have used information systems for operations processes that manually become an automated and integrated system. One of which is a parking system. In Indonesia there are still many vehicle day care stations that use a parking system manually. This makes the parking attendant unfamiliar with the price set and the lengths of time parked the vehicle and make it difficult in the process of calculating the report of parked vehicles. For this reason, an integrated parking system is needed so that it can be applied to manual vehicle storage. So in making the parking system uses the concept of programming. The concept of the program to be used is the concept of Object Oriented Programming with the Java programming language and the editor uses Netbeans 8.2 to run the program. The method in conducting this research is to use 2 methods, namely the method for collecting data with the description method and the method for developing a waterfall system. With the parking system will provide convenience for parking users and also make efficient parking attendant performance. So expect speed, and accuracy in collecting vehicle parking at a vehicle storage in Indonesia.